FTTx networks : technology implementation and operation - Farmer, James, 1944-; Lane, Brian; Bourg, Kevin; Wang, Weyl (Morgan Kaufmann, 2017)
FTTX Networks: Technology Implementation and Operation provides an in-depth treatment of the technology and implementation of FTTX networks, discusses the environment that gave rise to FTTX, provides a survey of the available FTTX technologies, and gives users the state-of-the-art knowledge needed for successful deployment of FTTX. The book includes hands-on project planning engineering design and operations checklists, as well as recommended best practices for configuring FTTH systems and the data networks preceding them for IPTV, voice, and data, with case studies of actual FTTH systems and a methodology for predicting the performance of real systems. This book is a must-read for all network engineers, technical businesspeople, and technical specialists engaged in building FTTX networks, from technology selection, to fielding the network in production, to implementation.